2010
DOI: 10.1677/erc-10-0076
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and risk of endometrial cancer: a systematic review

Abstract: More than 15 case-control studies and at least four large cohort studies demonstrated a decrease in the risk of endometrial cancer of about 50% for ever use of combined oral contraceptives (COCs). In most of these studies, this protective effect persisted for more than 10-15-20 years after cessation of the COC. An increasing protective effect with longer duration of COC use has been found in most studies. The beneficial effect was independent of the composition of COC, i.e. dosage and type of progestogen, comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 48 publications
4
36
0
3
Order By: Relevance
“…Two different clinicopathological subtypes of endometrial cancer are recognized: one is estrogen-related type 1 (endometroid), and the other is non-estrogen-related type 2 (non-endometroid such as papillary serous and clear cell) (1). Although various endocrine, genetic and external factors, such as unopposed estrogen exposure, complex hyperplasia with atypia, and treatment with tamoxifen during breast cancer therapy, may contribute to its initiation and progression, the etiology of endometrial carcinoma remains not fully understood (2).…”
Section: Introductionmentioning
confidence: 99%
“…Two different clinicopathological subtypes of endometrial cancer are recognized: one is estrogen-related type 1 (endometroid), and the other is non-estrogen-related type 2 (non-endometroid such as papillary serous and clear cell) (1). Although various endocrine, genetic and external factors, such as unopposed estrogen exposure, complex hyperplasia with atypia, and treatment with tamoxifen during breast cancer therapy, may contribute to its initiation and progression, the etiology of endometrial carcinoma remains not fully understood (2).…”
Section: Introductionmentioning
confidence: 99%
“…Mueck et al 24 recently published a review of all studies of the relationship between endometrial cancer and hormonal contraception. More than 15 case-control studies and at least four large cohort studies demonstrated a decrease in the risk of endometrial cancer of about 50% if COCs had ever been used.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Endometrial cancer is the most common gynecologic malignancy, and its occurrence is related to both endogenous and exogenous hormone exposures (1)(2)(3)(4). Combination oral contraceptives (COC) and menopausal hormone therapy are the most common forms of exogenous hormones.…”
Section: Introductionmentioning
confidence: 99%